IPng and the TCP/IP protocols implementing the next generation internet - Thomas, Stephen A. 1962 (John Wiley & Sons, 1996)
With the arrival of the new Internet protocols, TCP/IP and the Internet itself are undergoing some of the most drastic changes in their history. IPng and the TCP/IP Protocols gives computer and software engineers a complete description of the IPng or next generation Internet protocols, as well as the technical information key to its successful implementation. Detailed coverage begins with the latest network technologies, including Fast Ethernet, ISDN, and ATM LAN Emulation. The text continues with a thorough description of IPv6 and the new ICMP, as well as comprehensive and up-to-date coverage of transport, routing, configuration, and name service protocols. This book also contains the first detailed description of TCP/IP's real-time support, with chapters on RTP and RSVP. In addition, this invaluable reference previews future applications such as audio and video conferencing over the Internet, and it outlines the steps in a successful transition to IPng.